ДОБРОЧЕСНІСТЬ СУДДІВ ЯК ПРЕДМЕТ АДМІНІСТРАТИВНО-ПРАВОВОГО РЕГУЛЮВАННЯ - Жуков, Сергій Вікторович (SUPREMANCE OF LAW, 2019)
The article is devoted to the problem of determining the essence of the integrity of judges as a subject of administrative and legal regulation. The mechanism of administrative legal regulation and its elements are investigated in the work. The author pays special attention to the analysis of the instrumental approach in law. In terms of building the concept of administrative and legal regulation of the integrity of judges, the main advantage of the instrumental approach is the direct and fairly open nature of the relationship between the goal (task) and the consequences of the use of certain legal means, as well as the priority for a specific result, which has a high level of social significance. The author argues that the administrative-legal mechanism for regulating the integrity of judges will include a system of legal means aimed at creating an optimal model for the conduct of judges and enshrined in the norms of administrative legislation. The article contains the definition of three aspects of the category being studied and its concept, based on the provisions of the instrumental approach in law. The author formulates the concept of judges’ integrity as a subject of administrative and legal regulation: this is the model of the desired result, the functional state of the judicial system and the result of the implementation by the authorized state bodies of their competence in the form of a high degree of compliance with the requirements of the actual behavior of judges. Directions for further research should be to determine the administrative and legal status of the Public Council of integrity, deficiencies in administrative and legal regulation, lead to the inhibition of its work, and the preparation of proposals and recommendations for improving the administrative and legal support of the activities of this institution.